Agricultural productivity growth in Brazil: Large and small farms excel - Rada, Nicholas; Helfand, Steven; Magalhaes, Marcelo [UNESP] (Elsevier B.V., 2019)
The long-standing debate on the relationship between farm size and productivity has been generally limited by the range of farm sizes evaluated and the definition of productivity. In this paper we use data from three Brazilian agricultural censuses to address these issues. In particular, we introduce a wider distribution of farm sizes than presently available from the literature and we employ total factor productivity (TFP) as our performance measure. In doing so, we test which farm size class had the highest TFP levels in 1985 and 2006, how factor productivity growth varied within and across farm size classes between those years, and which policy or factor had the greatest productivity enhancing effect. When examining TFP growth, we move beyond the common decomposition into technical and efficiency changes by identifying the complete distribution of farm productivity performances. We find that by 2006 a U-shaped distribution of productivity over farm sizes had emerged. Considerable 1985-2006 TFP growth differences are prevalent; positive rates for the majority accompany stagnant or negative rates for some. Public education investments were associated with faster productivity growth regardless of farm size, while technical assistance's positive effect and credit's negative effect were associated with larger farm sizes. The role of specialization varied by size.
Keywords: Agriculture; Brazil; Efficiency; Farm size; Technical change; Total factor productivity (TFP)